Technology to Facilitate Progress Monitoring of Infant–Toddler Growth and Development: Measuring Implementation in Community-Based Agencies. Issue 2 (June 2023) - Buzhardt, Jay; Leonard, Julia; Ai, Jun; Higgins, Susan; Greenwood, Charles; Consolver, Kyle; Walker, Dale; Carta, Judith
Despite evidence that frequent progress monitoring to identify children at-risk of delays and inform early intervention services improves child outcomes, this practice is rare in infant–toddler settings where children could benefit the most from early intervention. Using a descriptive research design within an Implementation Science framework, we evaluated how 10 community-based infant–toddler agencies implemented a standardized progress monitoring assessment using a web application to monitor children's growth and identify children at-risk for delay. An Implementation Index was developed to quantify implementation progress for each agency, which included their percent of tasks completed, and rate of task implementation over time. Staff turnover and high staff:child ratios were associated with low implementation of progress monitoring. The Implementation Index differentiated between agencies that otherwise demonstrated similar implementation rates. Implications for supporting progress monitoring and other evidence-based practices in community-based infant–toddler childcare settings are discussed.